Meningkatkan Keterampilan Menulis Huruf Tegak Bersambung melalui Metode Demontrasi pada Siswa Kelas II-A di SD Negeri Gunung Picung 03 Pamijahan Kabupaten Bogor - Eneng Sri Anisa Widodo; Muzhir Ihsan (Primer Edukasi Journal, 2022)
This research aims to improve the ability to write cursive letters in class II-A students at SDN Gunung Picung 03 for the 2018-2019 school year. The subjects of this research were 26 students of class II-A at SDN Gunung Picung 03. The object of this research is the skill of writing cursive letters. The data collection methods used in this research are observation, tests and documentation. Observation was used to obtain data regarding the process of learning activities for writing cursive letter skills using the demonstration method. The test is used to determine students' abilities in writing cursive letters. Documentation is used as evidence that the research was properly carried out. The data analysis technique used in this research is quantitative descriptive. The research results showed an increase in the process of writing skills in cursive letters. Improving skills in writing cursive letters is characterized by increased neatness in writing, accuracy and appropriateness in writing cursive letters, fluency in reading and fluency in writing. The improvement in cursive writing skills that occurred was (1) the average score of students' ability in cursive writing skills was 58.4 with 30.8% completion. (2) the average value of cycle I is 63 with 61.5% completeness. (3) the average score for cycle II was 78 with 84.6% completeness. The difference in the increase in the average value from cycle I to cycle II is 23.9%